SIgA response and incidence of upper respiratory tract infections during intensified training in youth basketball players - Moraes, H.; Aoki, M. S.; Freitas, C. G.; Arruda, A. F. S.; Drago, G.; Moreira, A. (Biology of Sport, 2017)
The aim of the present study was to examine the effect of an intensified training phase followed by a tapering phase on the salivary immunoglobulin A concentration and on the upper respiratory tract infection (URTI) symptoms in young male basketball players. The session rating of perceived exertion method was used to quantify the internal training load, and the Wisconsin Upper Respiratory Symptom Survey-21 questionnaire was used to assess URTI symptoms. The Yo-Yo IR1 test and saliva collection were carried out at the beginning of the study (T1), after the intensified phase (T2), and after tapering (T3). A higher internal training load was observed for the intensified phase compared with the tapering phase (t=19.10; p<0.001), and a significant decrease in salivary immunoglobulin A concentration was detected (F=7.48; p=0.004) at T3 compared to T1 (p=0.02) and T2 (p=0.05). However, there was no significant difference between phases for severity of URTI (?2= 2.83; p=0.242). The Yo-Yo IR1 test performance increased from T2 and T3 compared to T1 (F=58.24; p<0.001). There was no significant effect of aerobic fitness level on salivary immunoglobulin A response (F=1.095; p=0.344). In summary, the present findings suggest that an intensified training load followed by a tapering period negatively affects the mucosal immune function with no significant change in severity of URTI in young basketball players.